Pathology of a Governance Reform: An Analysis of the Failure of the White Paper on European Governance - Hallila, Jaakko (My University, 2005)
This study approaches governance reforms and concentrates more precisely on the White Paper on European governance published by the Commission of the European Communities in 2001. The White Paper was carefully planned and ambitious attempt to increase citizen participation and reorganize the power structure of the European Union. Nevertheless the most significant reforms of the White Paper were never implemented and the European governance failed. This research analyzes the failure of the European governance. The analyze is supplemented by explaining the contents of the White Paper, explaining the preparatory process and the decision-making of the White Paper from preparatory stage to the Laeken Inter Governmental Conference, describing the implementation process of the European governance, and analyzing the discussion associated to the subject. This research is unique since most of the knowledge on the European governance is based on the Commission’s own studies not concentrating on finding reasons for the failure. The theoretical part of this research defines the concepts of the governance reform and good governance. Governance reforms can be generally divided into reforms of processes and structural reforms. This division is explained and used in this study. Reform processes can be analyzed by their smaller elements and their effects on the functions of the organization. Certain tools such as Likert’s scale are used to evaluate the process of the European governance reform. This study relies methodologically entirely on qualitative secondary data document analysis. Principle of saturation is taken into consideration when the documents are selected for this research. Documents from the sources forgotten in the Commission’s researches are given special importance. Internet sources proved to be useful for finding most recent information on the issue. It became apparent that the contents of the structural reform were very significant explaining factors for the failure. This was discovered in many documents and especially in opinions of the academic contributors. Also the documents of the other EU decision-making institutions supported that the structural reforms were not widely accepted. Other significant factors for explaining the failure were Commission’s inner conflicts, too tight schedule of the reform, obstinacy of the Commission, Top-down approach of the White Paper, and contradictory objectives presented in the reforms of the European governance. The concrete setback of the White Paper begun, when it met with fierce opposition from the behalf of the Parliament. The result of the Laeken IGC was an inevitable continuation to that. Laeken Declaration which did not include any of the structural reforms of the White Paper was a small consolation for the Commission. After all the process is a good example of how carefully done preparatory work is not enough for a successful governance reform. Compromises and wide acceptance is often necessary for the success.
Keywords: Governance; reform; Commission; European Union; fi=Hallintotiede : European Civil Servants - kansainvälisen hallinnon ohjelma|